2017
DOI: 10.1016/j.amepre.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Trial of a Personalized Multi-Condition Risk Assessment in Primary Care

Abstract: Introduction Personal risk for multiple conditions should be assessed in primary care. This study evaluated whether collection of risk factors to generate electronic health record (EHR)-linked health risk appraisal (HRA) for coronary heart disease, diabetes, breast cancer, and colorectal cancer was associated with improved patient–provider communication, risk assessment, and plans for breast cancer screening. Methods This pragmatic trial recruited adults with upcoming visits to 11 primary care practices duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Second, it is the first study to identify, in a sample of women recruited from the general population, possible defensive processing of real breast cancer risk information provided by a highly-publicized Internet-based risk assessment tool. Third, it demonstrates that a publically-available, widely used breast cancer risk assessment tool is associated with higher accuracy of risk perceptions in a way consistent with risk assessment tools used in clinical settings (48), thereby demonstrating a potentially significant impact at the population level. Our research also expands on prior research by assessing several key mediators of behavior change in a single model.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Second, it is the first study to identify, in a sample of women recruited from the general population, possible defensive processing of real breast cancer risk information provided by a highly-publicized Internet-based risk assessment tool. Third, it demonstrates that a publically-available, widely used breast cancer risk assessment tool is associated with higher accuracy of risk perceptions in a way consistent with risk assessment tools used in clinical settings (48), thereby demonstrating a potentially significant impact at the population level. Our research also expands on prior research by assessing several key mediators of behavior change in a single model.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, other recently-published research also reported that personalizing risk information can improve accuracy in some circumstances. (48) Nevertheless, we cannot draw causal inferences about changes in risk perception accuracy or defensive processing from our data. Future research should explore these issues using a true experimental design.…”
Section: Discussionmentioning
confidence: 84%
“…To fill a need created by the legislation, providers want tools to help promote informed decision-making about MBD and breast cancer screening. 10 While several studies have examined decision tools to systematically identify breast cancer risk in clinical settings and to increase patient-PCP discussion of breast cancer risk, 14,17,18 we do now know of studies to date that have specifically examined the role of MBD notification on decision-making, although studies are underway. 19 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous FHL studies have noted a need for better clinical integration [2], and our results suggest people would find features such as saving and updating information in FHL useful; many participants stated a desire to save, edit, and share their information with family members. Integration with electronic medical records is available in some generalized risk assessment tools [68, 69], but is not standard across tools and has been identified as a key reason for why family health history tools are not yet ready to be implemented in clinical settings [8]. Several participants reported they would share their FHL risk assessment with a physician; however, as a study of the James Link tool showed [19], some suggested they would do so only if FHL indicated they were at high or above-average risk of cancer or CHD.…”
Section: Discussionmentioning
confidence: 99%